Unhealthy diet practice and symptoms of stress and depression among adolescents in Pasir Gudang, Malaysia - Tajika, Esra; Abd Latiff, Latiffah; Awang, Hamidin; Adznam, Siti Nur ‘Asyura; Chin, Yit Siew; Abu Bakar, Azrin Shah; Koh, Patricia Chai Hsia; Che Ghazali, Mohd Izudin Hariz (Elsevier, 2016)
Background/objective: Missing main meals and an unhealthy snacking pattern can lead to poor diet quality and consequently to the presence of chronic diseases among which mental disorder is no exception. Since there is little research on diet, skipping meals and psychological status in Asian countries, this study tries to determine eating behaviour and predicting symptoms of stress and depression of adolescents in Pasir Gudang, Malaysia.